The Combination of Peer and Self-directed Feedback on Writing Ability of EFL High Proficient Students - Rizky Amelia; Mohammad Adnan Latief; Enny Irawati (Pascasarjana UM, 2018)
Abstract: This study examined whether high proficient students who are trained with the treatment of the combination of peer and self-directed feedback (PSF) have better writing ability than the high proficient students who are not trained with this treatment. Employing a quasi-experimental research, this study involved two groups of 28 students given a writing test. The results pointed out that the students who were trained with the combination of PSF had better writing ability than the students who were not trained with the combination of PSF. Teachers are suggested to provide the combination of PSF to high proficient students. Further investigation involving moderate and low proficiency levels is suggested.Key Words: peer and self-directed feeedback, writing ability, English proficiencyAbstrak: Penelitian ini menguji apakah mahasiswa yang dilatih dengan perlakuan kombinasi umpan balik dari teman sebaya dan diri sendiri (PSF) memiliki kemampuan menulis yang lebih baik daripada mahasiswa yang tidak dilatih dengan perlakuan kombinasi umpan balik dari teman sebaya dan diri sendiri. Dengan desain kuasi eksperimental, penelitian ini melibatkan dua kelompok dengan 28 mahasiswa yang diberi tes menulis. Hasil menunjukkan bahwa mahasiswa yang dilatih dengan kombinasi PSF memiliki kemampuan yang lebih baik daripada mahasiswa yang tidak dilatih dengan kombinasi PSF. Guru disarankan memberikan perlakuan ini pada siswa yang mahir berbahasa Inggris. Penelitian lanjutan melibatkan kemahiran bahasa Inggris sedang dan tinggi pun disarankan.Kata kunci: umpan balik teman sebaya dan diri sendiri, kemampuan menulis, mahir berbahasa Inggris